Effect of pain reduction on postural sway, proprioception, and quadriceps strength in subjects with knee osteoarthritis. Issue 5 (1st May 2002) - Hassan, B S; Doherty, S A; Mockett, S; Doherty, M
Abstract : Objective: To investigate whether alleviation of knee pain influences quadriceps function, proprioceptive acuity, and postural stability in patients with knee osteoarthritis (OA). Methods: A crossover, within-subject, double blind study design involving 68 subjects with painful knee OA. Each subject received an intra-articular injection into one or both knees (both if symptomatic) of either 5 ml 0.5% bupivacaine or 5 ml 0.9% saline. Two weeks later they received an injection of the alternative agent. Subjects and observer were unaware of the order of injection, which was randomly assigned. Knee pain (100 mm visual analogue scale), static postural sway, knee proprioceptive acuity, maximum voluntary contraction (MVC), and percentage activation of the quadriceps were assessed immediately before and one hour after each injection. Results: Significant pain reduction was achieved one hour post-bupivacaine (mean difference as a percentage change 56.85, 95% CI 31.01 to 73.65; p<0.001) and post-saline (mean difference as a percentage change 41.94, 95% CI 11.57 to 76.66; p< 0.001), with no significant difference between the two. Both MVC and activation increased significantly post-bupivacaine (mean percentage differences 18.83, 95% CI −31.79 to −0.26, and −11.90, 95% CI −39.53 to 2.97, respectively; both p<0.001) and post-saline (mean percentage differences −7.64, 95% CI −21.96 to 4.73, and −10.71, 95% CI −25.19 to 2.60 respectively; both p<0.001). Proprioception worsened after bupivacaine (mean percentage difference −28.15%, 95% CI −83.47 to 19.74; p=0.009), but there was no effect on postural sway; saline injection had no effects. There was no order effect, and comparison of median percentage changes showed no significant differences between injections for change in MVC, activation, proprioception, or sway. Conclusion: Reduction in knee pain through either peripheral (local anaesthetic) or central (placebo) mechanisms resulted in increased MVC. This increase, however, did not result in improvements in proprioception or static postural stability, suggesting that other mechanisms play a part in these functions, at least in this acute model.